The contribution of the nurse manager to healthy labour relations parts - Marthie Bezuidenhout (AOSIS, 1998)
From the discussion in part one of this article, it was clear that labour unrest has had a detrimental effect on the provision of health care in South Africa. Opsomming Vanuit die bespreking in deel een van die artikel is dit duidelik dat arbeidsonrus 'n negatiewe effek op die voorsiening van gesondheidsorg in Suid-Afrika gehad het. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.